Simulation of Solar Cell Diode I-V Characteristics Using Finite Element Methode: Influence of p- Layer Thickness - Greta Andika Fatma; Endhah Purwandari; Edy Supriyanto (UNEJ e-Proceeding, 2016)
Characteristic of I-V is a key parameter of describing the performance of solar cell diode, specially for Silicon material. One of the effort to get its higher performance can be conducted by investigating the effect of the thickness of p-layer. The thickness becomes important factor because of its function as windows layer, which will determine the number of generation factor, appropiate to the charge carrier producing. Here, we explore them by using computer program, applying finite element methode as the numerical simulation. The geometry of the diode was simulated in one dimensional structure, where the thickness of p-layer varied from 0,7 μm to 1,5 μm, while the n-layer was fixed at a thickness of 3,5 μm. The result showed that the optimum parameters has come out to achieve the best performance of this type of solar cell.